2020
DOI: 10.1039/d0ta06524b
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing surface states in hematite nanorod photoanodes, both beneficial and detrimental to solar water splitting efficiency

Abstract: The perfomance of hematite and Ti-substituted hematite nanorods as photoanodes for solar water splitting was quantitavely evaluated from photoelectrochemical point of view. The nanostructure, morphology and chemical / electronic structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 81 publications
4
66
0
Order By: Relevance
“…Here, we report on intrinsic heterostructuring owing to surface segregation of a Ti-rich phase during the annealing under Nitrogen of Ti-doped hematite photoanodes obtained by aqueous growth [14]. For these photoanodes we recorded strong enhancement of the photocurrent and lower flat-band values, compared to air-annealed samples.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Here, we report on intrinsic heterostructuring owing to surface segregation of a Ti-rich phase during the annealing under Nitrogen of Ti-doped hematite photoanodes obtained by aqueous growth [14]. For these photoanodes we recorded strong enhancement of the photocurrent and lower flat-band values, compared to air-annealed samples.…”
Section: Introductionmentioning
confidence: 90%
“…However, pristine hematite presents low SWS efficiency because of the reduced hole mean free path (~ 2 -4 nm) and poor surface kinetics related to a complex oxygen evolution reaction (OER) [1][2][3][4][5]. It was largely demonstrated that surface kinetics during SWS can be tuned by controlling surface states nature using various band engineering approaches: doping [6][7][8], hetero-and nano-structuring [9][10][11][12][13], annealing [14,15], catalyst film coating [16][17][18][19][20][21], etc. In particular the synergic effect between Ti-doping and induced oxygen vacancies through thermal treatments during or post growth under oxygen depleted atmosphere has shown its efficiency [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the SS of a surface is controlled by its chemical nature, surface reaction, adsorbed species, and surface defects in catalysts. Hence, when illuminated, SS consisting of trapped holes and electrons are what cause the reactions on the surface of the catalysts. Using an AC signal, the nature of the SS of given materials may be investigated under equilibrium or steady-state conditions since photocatalysis and the PEC process are relatively faster in rate. However, surface trapped charged species under equilibrium and steady-state conditions may not give the real mechanism by which the reaction catalyzed by a photocatalyst or a photoelectrocatalysts occurs.…”
Section: Alternating Current Techniques For Pc and Pec Interfacesmentioning
confidence: 99%
“…The process of solar water splitting requires photoanode materials with suitable band gaps and excellent stability. Iron oxide (Fe 2 O 3 ) is considered to be the photoanode material that has the most potential application possibility. α-Fe 2 O 3 is the most thermodynamically stable phase among the four phases of Fe 2 O 3 (α, β, γ, and ε) and has been studied as a traditional photoanode material in the past few decades. Researchers have spent a great deal of effort on the factors that limit its photoelectrochemical performance and have proposed methods to solve these problems. The saturation photocurrent density of the α-Fe 2 O 3 photoanode can reach 4 mA cm –2 , and the onset potential can be reduced to 0.6 V RHE . This performance is still far from its practical application in photoelectrochemical cells. As the research on α-Fe 2 O 3 photoanodes encountered a bottleneck, the enthusiasm of researchers for α-Fe 2 O 3 photoanodes subsided and their attention turned to metastable Fe 2 O 3 . …”
Section: Introductionmentioning
confidence: 99%